OS FANTASMAS DO CAMPO: UM ESTUDO DO FANTÁSTICO EM MAURO RÊGO - SANTOS, Tenyse Pinto Meneses (2024)
This research analyzed the work Os Fantasmas do Campo (2018) and (2009) by Mauro Rêgo through the lens of fantastic literature studies, identifying the elements that position it within the Maranhense fantastic mode. Based on the theoretical frameworks of Todorov (1981), Furtado (1980), Roas (2014), García (2007), Bessière (1974), Cascudo (2012), and Ceserani (2006), among others, the investigation employed a descriptive and qualitative approach grounded in bibliographic review. The process included cataloging the book's stories according to three main themes: natural elements, zoomorphism, and devotional practices. The research was structured into three main sections. Initially, it addressed the developments of the fantastic over time, contextualizing its evolution in literature. Next, it focused on the fantastic within the Maranhense context, highlighting its regional specificities. Finally, it discussed the inclusion of Os Fantasmas do Campo in literary criticism as a representative example of the Maranhense fantastic. The results confirmed that the work incorporates essential characteristics of the fantastic mode, particularly by valuing the historical and cultural traditions of Anajatuba, Maranhão. Oral narratives passed down through generations, combined with the use of local expressions, bring readers closer to regional experiences, while the themes explore the supernatural in harmony with local culture. Additionally, the emphasis on natural aspects and regional beauty enriches Maranhão’s literary landscape. It is concluded that Os Fantasmas do Campo stands out as a significant work within the scope of Brazilian fantastic literature, reaffirming the importance of regional literature in the national panorama. The research concluded by demonstrating how Mauro Rêgo contributes to the strengthening of Maranhão’s literary tradition, innovatively integrating local cultural elements into the fantastic mode.